Ovulation induction with clomifene: a primary care perspective. Issue 1 (7th August 2011) - Wilkes, Scott; Murdoch, Alison
Abstract : Infertility affects one in seven couples during their lifetime. Approximately one-quarter of these will have an ovulatory disorder contributing to their inability to conceive. Ovulatory disorders represent the simplest form of infertility to treat, and where this is not a result of ovarian failure or poor ovarian reserve most women require ovulation induction with clomifene citrate (CC). This review aims to examine the role of CC in a general practice setting. CC is a simple, relatively safe, easily administered and well-tolerated efficacious drug. There is, however, a 10% risk of multiple births associated with its use. CC has been used in general practice for many years and continues to be used. Currently, guidelines do not describe its use in the general practice setting and the evidence for monitoring its use with mid-luteal progesterone estimation or ultrasound scanning is conflicting.